Chicken Nuggets Quality Affected by the Egg White Addition - Herly Evanuarini (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2010)
One of the binding agent which could be used in the production of chicken nuggets is egg white. The different frying temperature and time will result in different physical, chemical and nutritional quality. The aim of this study was to find out the effect of addition egg white to the nuggets' quality. This research consisted of one level of experiment was designed in Fully Randomized Design. TheÂ  experiment result showed that the best product was produced by adding 10 % egg white. This product had hardness value of 30.10 N, Cutting stress: of 5.13 N, elasticity of 0.333 s/g, and the organoleptic score for texture and taste were 6.50 and 6.44 respectively. Â  Keywords: Chicken nuggets, egg white